The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s10162-018-0656-x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Effects on Monaural Amplitude-Modulation Sensitivity in Ipsilateral, Contralateral and Bilateral Noise

Abstract: The amplitude modulations (AMs) in speech signals are useful cues for speech recognition. Several adaptation mechanisms may make the detection of AM in noisy backgrounds easier when the AM carrier is presented later rather than earlier in the noise. The aim of the present study was to characterize temporal adaptation to noise in AM detection. AM detection thresholds were measured for monaural (50 ms, 1.5 kHz) pure-tone carriers presented at the onset ('early' condition) and 300 ms after the onset ('late' condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 62 publications
0
19
1
Order By: Relevance
“… Smith et al (2000) demonstrated that, in macaques, the tone threshold increment with CAS remained to some extent when MOC efferents were sectioned. Marrufo-Pérez et al (2018) showed that detection thresholds for short (50 ms) tones increased more when the tone and CAS onset coincided (early condition) than when the tone onset was delayed 300 ms from the CAS onset (late condition). Because the time course of MOCR activation is around 300 ms ( Backus and Guinan, 2006 ), one would expect greater threshold increments in the ‘late’ than in the ‘early’ condition if the MOCR were the only responsible for the increments, but this was not the case.…”
Section: Discussionmentioning
confidence: 99%
“… Smith et al (2000) demonstrated that, in macaques, the tone threshold increment with CAS remained to some extent when MOC efferents were sectioned. Marrufo-Pérez et al (2018) showed that detection thresholds for short (50 ms) tones increased more when the tone and CAS onset coincided (early condition) than when the tone onset was delayed 300 ms from the CAS onset (late condition). Because the time course of MOCR activation is around 300 ms ( Backus and Guinan, 2006 ), one would expect greater threshold increments in the ‘late’ than in the ‘early’ condition if the MOCR were the only responsible for the increments, but this was not the case.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that different efferent time constants may be required in different listening situations [27]. A number of studies suggest that efferent activation may play a role in the perception of amplitude modulation in general [47] and in human speech perception [48], [49], although the effect of different background noise-type and time constants has not been explicitly assessed. Recent studies with a binaural cochlear implant sound coding strategy with efferent-inspired feedback also demonstrate improved speech intelligibility in noise with very short efferent time constants [50].…”
Section: Discussionmentioning
confidence: 99%
“…Marrufo-P erez et al (2018a) discussed that such an effect could allow the basilar membrane to follow the dips and peaks in amplitude-modulated waveforms and improve encoding of such signals (see Fig. 1A in Marrufo-P erez et al, 2018a). Modulations in the waveform of speech carry important information on place, manner, and voicing (Rosen, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The human auditory system contains a rich efferent network wherein the cortex modulates brainstem activity, and the brainstem influences cochlear activity. The auditory efferent system improves detection of sounds in background noise, reduces auditory damage due to high-intensity sound exposure, and may be involved in selective attention (for recent reviews, see Guinan, 2018;Lopez-Poveda, 2018). The medial olivocochlear (MOC) branch of the auditory efferent system innervates the outer hair cells (OHCs), which are responsible for cochlear amplification (for a review of cochlear amplification, see Ashmore, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation